Reproductive Ability of Currant–Gooseberry Hybrids After Cryopreservation of Pollen in Liquid Nitrogen - O., A. Tikhonova; A., A. Khokhlenko; V., G. Verzhuk (Journal of Agronomy Research, 2025)
The present study of the reproductive ability of currant and gooseberry hybrids after long-term cryopreservation of pollen in liquid nitrogen is of enormous importance for organizing the conservation of the diversity of this crop. Four distant interspecific hybrids of currant and gooseberry served as objects of the study. The pollen fertilizing ability was studied by pollination of allotetraploid Jošta with pollen of tetraploid hybrids stored for a year at ultra-low temperatures (–196°C) and freshly collected pollen (control pollination). Berry set in 2022, when pollinated with cryopreserved pollen, averaged 56.4% and was higher than in the control pollination (38.2%). In 2023, the number of berries set on average for all cross combinations in the experiment was also quite high (59.6%), but lower than in the pollination control (81.4%), which can be explained by unfavorable weather conditions during pollen collection in the year of establishment (2022). The obtained data specify that pollen of the allotetraploids does not lose its high fertilizing ability during its long-term cryopreservation. Berry setting, average berry weight and seed production are quite high and comparable to pollination with freshly collected pollen (control pollination variant). Seed germination and values of morphometric parameters of seedlings obtained from pollination with cryopreserved and freshly collected pollen in most cases have close values. Cryopreservation of pollen of currant-gooseberry hybrids for a year and more allows to preserve pollen for successful pollination and berry formation and is a reliable way to preserve germplasm.
Keywords: allotetraploid; pollination; long-term cryopreservation; berry setting; berry weight; seed productivity